Evaluation of the Cytotoxicity and Biocompatibility of New Resin Epoxy–based Endodontic Sealer Containing Calcium Hydroxide - Cintra, Luciano Tavares Angelo [UNESP]; Benetti, Francine [UNESP]; de Azevedo Queiroz, Índia Olinta [UNESP]; Ferreira, Luciana Louzada [UNESP]; Massunari, Loiane [UNESP]; Bueno, Carlos Roberto Emerenciano [UNESP]; de Oliveira, Sandra Helena Penha [UNESP]; Gomes-Filho, João Eduardo [UNESP] (Elsevier, 2017)
Introduction Many endodontic sealers are available, but the search for the ideal sealer continues. This study evaluated the cytotoxicity and biocompatibility of Sealer Plus, a new resin epoxy–based endodontic sealer containing calcium hydroxide. AH Plus, Endofill, and SimpliSeal endodontics sealers were used for comparison. Methods L929 fibroblasts were cultured, and an MTT assay was used to determine the cytotoxicity of the sealer extracts at 6, 24, 48, and 72 hours. Tubes containing materials or empty tubes for control were inserted into the subcutaneous tissues of 20 rats. After 7 and 30 days, the rats were killed, and the tubes were removed with the surrounding tissues for histologic analysis. The data were submitted to statistical tests (P <.05). Results Undiluted Sealer Plus exhibited less cytotoxicity compared with other undiluted extracts at 6 hours (P <.05), and cell viability was higher for all Sealer Plus extracts after 24 hours (P <.05). At 48 hours, the undiluted and ½ Sealer Plus dilution were the extracts with less cytotoxicity (P <.05). At 72 hours, cell viability was higher for the undiluted and ½ Sealer Plus dilution compared with the other sealers (P <.05). At 7 days, Endofill and SimpliSeal had higher inflammation compared with the control and Sealer Plus (P <.05); AH Plus had moderate inflammation (P >.05). At 30 days, control, Sealer Plus, and AH Plus had less inflammation (P <.05). The fibrous capsule was thick at 7 days and thin at 30 days, except for SimpliSeal. Conclusions In general, Sealer Plus promoted greater cell viability and was more biocompatible compared with the other sealers.
Keywords: Biocompatibility; calcium hydroxide; cytotoxicity; endodontic sealers; resin epoxy